Early Christian archaeology in Hungary between 2010 and 2016 - Nagy , Levente (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In 2010 the Department of Archaeology at the University of Pécs witnessed the establishment of Christian Archaeology, a new M.A. subject that did not exist in Hungary before. Shortly after the launch of Christian Archaeology in Hungary, in 2012 the department started a new research project in collaboration with the Department of Christian Archaeology, University of Vienna, under the title Frühes Christentum in Ungarn. This contribution is a presentation of the most important events and research-results in Christian Archaeology in Hungary between 2010 and 2016. Recent publications of the Roman provincial archaeologists, migration period archaeologists and patristic philosophers and theologians are also taken into account.